Ectoparasites of Didelphis virginiana From Yucatan, Mexico. Issue 6 (6th June 2020) - Canto-Osorio, Juan Miguel; Cuxim-Koyoc, Alan; Ruiz-Piña, Hugo A; Morales-Malacara, Juan B; Reyes-Novelo, Enrique
Abstract: A faunal study is presented to determine the species of ectoparasites found in the opossum Didelphis virginiana (Kerr) (Marsupialia: Didelphidae). For this, Tomahawk traps were placed in the peridomiciles of a rural town in Yucatán, to capture individuals of this marsupial and proceed to the collection of their ectoparasites. A total of 3, 023 arthropods were collected from 145 opossums. The most frequent ectoparasites were the acarines Ornithodoros ( Alectorobius ) nr. talaje (64.8%) (Argasidae); Ornithonyssus wernecki Fonseca (53.8%) (Macronyssidae) and Didelphilicus serrifer Fain (25.5%) (Atopomelidae); the ticks Amblyomma parvum Aragão (8.3%) and A. mixtum Koch (10.3%) (Ixodidae); and the fleas Ctenocephalides felis (Bouché) (20.7%) and Pulex simulans Baker (8.3%) (Pulicidae). It is concluded that the ectoparasite fauna of this marsupial is mainly composed of euryxenous organisms, which have been documented as vectors of diseases caused by rickettsial bacteria. Since D. virginiana is widely adapted to the peridomiciliary environment in the region, this study allows recognizing those that represent a potential risk for the transmission of vector-borne zoonotic diseases.